RETRACTED: Snail Consumption Pattern in Ibarapa Central Local Government of Oyo State, Nigeria - T.O. Babatunde; O.O. Babatunde; A.R. Aduloju; T. Oluwalana (Journal of Applied Sciences and Environmental Management, 2020)
This article has been retracted by the Editor.